1
$\begingroup$

Find the following limit without using the L'Hopital rule: $$\lim_{n\to\infty} \left(\dfrac{\sqrt{n^2+n}-1}{n}\right)^{2\sqrt{n^2+n}-1}$$

Answer: $e^{-1}$

My attempt: Since the limit is of the form $1^{\infty}$, I decided to use the standard formula:

$$\lim_{x\to a} f^g = e^{\lim_\limits{x\to a}(f-1)g}$$

(See link)

Let $l=(f-1)g$.

We have, $$l=\left(\dfrac{\sqrt{n^2+n}-(1+n)}{n}\right)(2\sqrt{n^2+n}-1)$$ This on solving boils down to $$l=2n+3-\sqrt{1+\frac 1n}(2n+3)+\frac 1n$$ Now if I tend $n$ towards infinity, then $l\to 0$ and the limit i.e. $e^l$, is equal to $1$, which contradicts the given answer.

Please help. Thanks!

Edit: A proof for the "standard formula" I have used.

enter image description here

Edit 2: just noticed a typo in the power which I have now fixed.

$\endgroup$
  • 1
    $\begingroup$ Can you explain why $$\lim_{x\to a} f^g = e^{\lim_\limits{x\to a}(f-1)g}?$$ The only formula resembling that I'm familiar with is $$f^g = e^{g \ln(f)}$$ $\endgroup$ – Eevee Trainer May 16 at 6:01
  • 1
    $\begingroup$ @Eevee Trainer see this post. I have also added the very same link to the question. $\endgroup$ – AryanSonwatikar May 16 at 6:08
3
$\begingroup$

$ \lim_{n \to \infty} l = -1 $, not $ 0 $. Indeed, \begin{align} 2n + 3 - \sqrt{1 + \frac{1}{n}}(2n + 3) + \frac{1}{n} &= \left(1 - \sqrt{1 + \frac{1}{n}}\right)(2n + 3) + \frac{1}{n} \\ &= \frac{(1 - \sqrt{1 + 1/n})(1 + \sqrt{1 + 1/n})}{1 + \sqrt{1 + 1/n}} \cdot (2n + 3) + \frac{1}{n} \\ &= \frac{-1/n}{1 + \sqrt{1 + 1/n}} \cdot (2n + 3) + \frac{1}{n} \\ &= - \frac{2 + 3/n}{1 + \sqrt{1 + 1/n}} + \frac{1}{n} \\ &\to -1 \end{align} as $ n \to \infty $.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Okayyy. Thanks a lot. So my mistake was to assume $1-\sqrt{1+\frac 1n}$ to be $0$. $\endgroup$ – AryanSonwatikar May 16 at 6:31
2
$\begingroup$

$$a_n=\left(\frac{\sqrt{n^2+n}-1}{n}\right)^{2\sqrt{n^2+n}-1}\implies\log(a_n)=\left({2\sqrt{n^2+n}-1}\right)\log\left(\frac{\sqrt{n^2+n}-1}{n}\right)$$ Now, using Taylor expansions $$\log\left(\frac{\sqrt{n^2+n}-1}{n}\right)=-\frac{1}{2 n}-\frac{1}{4 n^2}-\frac{1}{24 n^3}+O\left(\frac{1}{n^4}\right)$$ $${2\sqrt{n^2+n}-1}=2 n-\frac{1}{4 n}+\frac{1}{8 n^2}-\frac{5}{64 n^3}+O\left(\frac{1}{n^4}\right)$$ $$\log(a_n)=-1-\frac{1}{2 n}+\frac{1}{24 n^2}+O\left(\frac{1}{n^3}\right)$$ $$a_n=e^{\log(a_n)}=\frac 1e \left(1-\frac{1}{2 n}+\frac{1}{6 n^2} \right)+O\left(\frac{1}{n^3}\right)$$ which shows the limit and how it is approached.

Moreover, this gives a shortcut estimation of $a_n$. Suppose $n=10$ $$a_{10}=\left(\frac{10}{\sqrt{110}-1}\right)^{1-2 \sqrt{110}}\approx 0.350040$$ while the truncated expansion gives $\frac{571}{600 e} \approx 0.350099$.

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

You can also do it by asymptotics. Indeed, using $\sqrt{1+1/n}= 1 + \frac{1}{2n} + \mathcal{O}(1/n^2)$ as $n\to\infty$. Your expression then simplifies as follows, $$\left(\frac{n\sqrt{1+1/n} - 1 }{n}\right)^{2n\sqrt{1+1/n} -1} = \left(1-\frac{1}{2n} + \mathcal{O}(1/n^2) \right)^{2n+\mathcal{O}(1/n)}\qquad \text{as } n\to\infty.$$ By using $a_n^{b_n} = e^{b_n\log a_n}$, the expression can be simplified to $e^{-1+\mathcal{O}(1/n)}= e^{-1}+\mathcal{O}(1/n)$. Hence the limit is $e^{-1}$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.